Functional reconstruction of injured corpus cavernosa using 3D-printed hydrogel scaffolds seeded with HIF-1α-expressing stem cells - An, Geng (Nat Commun, 2020)
Injury of corpus cavernosa results in erectile dysfunction, but its treatment has been very difficult. Here we construct heparin-coated 3D-printed hydrogel scaffolds seeded with hypoxia inducible factor-1α (HIF-1α)-mutated muscle-derived stem cells (MDSCs) to develop bioengineered vascularized corpora. HIF-1α-mutated MDSCs significantly secrete various angiogenic factors in MDSCs regardless of hypoxia or normoxia. The biodegradable scaffolds, along with MDSCs, are implanted into corpus cavernosa defects in a rabbit model to show good histocompatibility with no immunological rejection, support vascularized tissue ingrowth, and promote neovascularisation to repair the defects. Evaluation of morphology, intracavernosal pressure, elasticity and shrinkage of repaired cavernous tissue prove that the bioengineered corpora scaffolds repair the defects and recover penile erectile and ejaculation function successfully. The function recovery restores the reproductive capability of the injured male rabbits. Our work demonstrates that the 3D-printed hydrogels with angiogenic cells hold great promise for penile reconstruction to restore reproductive capability of males.